Fuzzy controller hardware implementation for an EV's HESS energy management - Hatim, Jbari; Rachid, Askour; Badr, Bououlid Idrissi (International journal of electrical and computer engineering systems, 2023)
The recent technological advances related to embedded systems, and the increased requirements of the Electric Vehicle (EV) industry, lead to the evolution of design and validation methodologies applied to complex systems, in order to design a product that respects the requirements defined according to its performance, safety, and reliability. This research paper presents a design and validation methodology, based on a hardware-in-the-loop (HIL) approach, including a software platform represented by Matlab/ Simulink and a real-time STM32 microcontroller used as a hardware platform. The objective of this work is to evaluate and validate an Energy Management System (EMS) based on Fuzzy Logic Controller (FLC), developed in C code and embedded on an STM32 microcontroller. The developed EMS is designed to control, in real-time, the energy flow in a hybrid energy storage system (HESS), designed in an active topology, made of a Li-ion battery and Super-Capacitors (SC). The proposed HESS model was organized using the Energetic Macroscopic Representation (EMR) and constructed on Matlab/Simulink software platform. The evaluation and validation of the developed algorithm were performed by comparing the HIL and simulation results under the New European Driving Cycle (NEDC).